Pelaksanaan Peralihan Hutang Yang Dijaminkan Dengan Hak Tanggungan Karena Pewaris Meninggal Dunia Menurut KUHPerdata - Adilla, Jihan; Munandar, Aris (Private Law, 2024)
This study aims to examine the arrangements of debt transfer due to the death of the testator guaranteed by a mortgage and the settlement of those cases according to the Civil Code. This research uses normative-empirical research. The conclusion showed that according to the Civil Code, the heir can determine whether he accepts, rejects, or accepts with conditions (benefisier). The methods of settlement according to the Civil Code were: if the heir accepted, then a novation (debt renewal) was carried out; if he refused, then an auction was carried out by the creditor; if he accepted with conditions, then he would be given the option to sell himself or be sold by the creditor.